PHYSICOCHEMICAL PROPERTIES AND MAJOR ELEMENTS CONTENTS OF ALGERIAN HONEYS FROM SEMI-ARID REGIONS - Haouam, Lynda; Tahar, Ali; Dailly, Hélène; Lahrichi, Anissa; Chaqroune, Abdellah; Abdennour, Cherif (Emirates Journal of Food and Agriculture, 2017)
The aim of this study is to characterize honeybees from semi-arid regions of North-east Algeria. Therefore, twenty artisanal honey samples (13 multifloral and 7 unifloral) were collected and then characterized on the basis of their physico-chemical parameters (free acidity, pH, moisture content, electrical conductivity, Ash and sugar content) and the mineral composition (Ca, K, Mg and Na). Results showed that these regions are characterized by low moisture and low percentage of major elements. However, potassium was the most abundant of all elements determined. A statistical analysis was carried out to identify the most signiﬁcant parameters and the chemometric methods used such as principal component analysis (PCA) and cluster analysis (CA) in order to classify the three types of honeys. The PCA indicated that the cumulative variance was 81.74% with the first four principal components variables. Therefore, the use of chemometric methods on the physico-chemical parameters and major elements is not a useful tool to characterize different types of honey originates regions with the same climate.